ADMINISTRATIVE INSTRUMENTS IN IMPLEMENTING FUNCTIONAL STRATEGIES COMPETITIVENESS MANAGEMENT - Stankovska , I. M. (The actual problems of regional economy development, 2017)
The article explores the use of аdministrative instruments in implementing functional strategies competitiveness management. Due to providing strategic financial management competitiveness the use of administrative levers of control in the formulation and implementation of financial strategies were investigated. System of financial policies forming by individual policies of general financial strategy, which is an administrative levers of influence on implementation strategies, was proposed. Structure strategic alternatives of financial and investment strategy implementation based on the decomposition and decision tree was formed. To select strategic alternatives, to identify strategic gaps and evaluate deviations from specified target markers in the implementation of financial policies using GAP-analysis that is a tool of management analysis was proposed.